2023
DOI: 10.1186/s12889-023-15940-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk of fracture according to temporal changes of low body weight changes in adults over 40 years: a nationwide population-based cohort study

Abstract: Background Low body weight is associated with an increased risk of fractures. However, the effect of temporal changes in the low body weight status on the risk of fracture remains unknown. This study aimed to evaluate the relationships between temporal changes in low body weight status and the risk of fractures in adults over the age of 40 years. Methods This study included data on adults over 40 years old who underwent two biannual consecutive gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…For example, Finkelstein et al reported a strong association between body mass index and the probability of sustaining an injury [ 25 ]. Vice versa, not obesity but underweight is a known risk factor for fractures, since obesity is usually not associated with an increased risk of fractures [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Finkelstein et al reported a strong association between body mass index and the probability of sustaining an injury [ 25 ]. Vice versa, not obesity but underweight is a known risk factor for fractures, since obesity is usually not associated with an increased risk of fractures [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%